Al-Shaykh Aḥmad al-Rifā‘ī wa Siyāqīyat al-Sharī‘ah al-Islamīyah: Dirāsah ‘alá Kitab Takhyirah - Islam, M. Adib Misbachul (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2012)
Kitab Takhyirah is a tarjumah book comprises of Kiai Ahmad Rifa'i Kalisalak's thoughts on Islam from its various aspects, such as 'aqidah, shari'ah, and akhlaq. The book consists about ideas that can be considered provocative in the context of Islamic thinking in the nineteenth century especially in Java and generally in Nusantara. Through Takhyirah, Kiai Ahmad Rifa'i has disseminated his notions on the unification of the various doctrinal aspects of Islam. He is different from the general ulama who tend to separate one aspect of Islam with other aspects. For example, Kiai Ahmad Rifa'i argued that Islamic syariah includes usul (akidah aspect), fiqh (Islamic law aspect), and tasawuf (akhlak and spiritual aspect).DOI: 10.15408/sdi.v19i1.372